2020
DOI: 10.1097/gox.0000000000002963
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-to-Nipple Distance in Selecting Patients for Nipple-sparing Mastectomy

Abstract: Introduction: Nipple-sparing mastectomy (NSM) is a valid option for carefully selected cases. Oncologic guidelines have not been established, but proximity of the tumor to the nipple, tumor size, lymph node involvement, and neoadjuvant chemotherapy have been suggested as contraindications to nipple preservation. This study describes our experience with NSM in relation to these factors, in particular distance of tumor from the nipple, to help establish evidence-based guidelines for NSM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Following established protocols for patient selection is vital when considering individuals for NSM candidacy. These protocols commonly involve criteria such as the absence of nipple involvement, tumor size, clinical examination results, lymph node involvement, and anatomical considerations [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following established protocols for patient selection is vital when considering individuals for NSM candidacy. These protocols commonly involve criteria such as the absence of nipple involvement, tumor size, clinical examination results, lymph node involvement, and anatomical considerations [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another parameter investigated for performing an NSM procedure is the tumor-to-nipple distance (TND). There is no strict range for TND, as it varies depending on the guidelines consulted [ 9 ]. A retrospective study compared patients who had a TND greater than 1 cm to those with a TND greater than 2 cm and found that there was no significant difference in the rate of NAC preservation among each group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst residual breast tissue is left behind in both SSM and NSM, 30 NSM also involves leaving a small amount of ductal tissue behind the nipple which could harbour occult malignancy or develop breast cancer in the future. Occult involvement of the NAC occurs in less than 5% of patients undergoing therapeutic mastectomy, and is associated with tumour size, grade, distance from the tumour to the nipple, and nodal positivity 7,31–34 . Consequently, an intra‐operative sample of retro‐areolar tissue may be sent for frozen section to exclude involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Occult involvement of the NAC occurs in less than 5% of patients undergoing therapeutic mastectomy, and is associated with tumour size, grade, distance from the tumour to the nipple, and nodal positivity. 7,[31][32][33][34] Consequently, an intra-operative sample of retro-areolar tissue may be sent for frozen section to exclude involvement.…”
Section: Dissatisfactionmentioning
confidence: 99%